ELEMENTS OF OCCUPATIONAL THERAPY IN KINETOTERAPEUTICAL PRACTICE - Andreea - Gabriela Lazăr (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Although occupational therapy is a separate field of therapy, certain specific elements, especially those related to the motricity sphere, support kinetotherapy. Kinetotherapy and occupational therapy do not oppose, but complement themselves. Some specialists consider occupational therapy as a means of kinetotherapy. Kinetotherapy recovers movement, and occupational therapy recovers the gesture. Any therapeutic activity wants to recover the patient physically and mentally, but it should not be omitted also the social return of the patient. As interdisciplinary science, occupational therapy supports other forms of therapy, primarily in the role of psychosocial therapy. Only by simultaneous action, the therapeutic methods can comprise the complexity of a human being, viewed as a biopsychosocial entity. The purpose of this research is to highlight the importance of occupational therapy in the complex recovery process, as well as the role of the means or forms specific to this therapy in the work of future kinetotherapists. I also want to point out some aspects that may lead to the enrichment of knowledge, therefore, the article may have a theoretical importance in the field of kinetotherapy.